Edukasi Self-Care Management Dan Positioning Untuk Mengatasi Nyeri Punggung Bawah Pada Pembatik Di Kampung Batik Laweyan - Arif Pristianto; Sarita Sri Astuti; Annisa Nur Syalfa; Retno Andriani; Rizki Nisaa’ Uljanah; Kharisma Puja Khusuma (Universitas 45 Surabaya, 2022)
Low back pain is a complaint in the form of pain or discomfort felt in the lower back and some spread to the legs, both right and left legs. Low back pain is often complained of by workers who sit a lot (sedentary jobs) such as batik craftsmen. Batik craftsmen or batik artisans are jobs that are carried out in a monotonous position, namely mostly sitting so that many complain of lower back pain. Sitting for long periods of time can cause tension in the lower back muscles. So that this tense muscle over time can cause complaints in the form of pain. The purpose of this activity is to provide education to the batik community about how to independently treat low back pain and the correct position when working as a batik maker. The target of this activity is batik in the village of Batik Laweyan, namely the Teko batik factory and Mahkota batik. The method used in this program is that students make observations or observations directly in the field, conduct dialogues and interviews using a screening form to 20 batik craftsmen. The results obtained are. The average batik maker in Batik Laweyan village complains of lower back pain. The conclusion of this activity is that the monotonous work position factor is very influential on lower back pain, especially those who work as batikmakers